Share Waqf (corporate Waqf) As An Alternative Financial Instrument In Improving The Communities And Nation Welfare - Khairil Faizal Khairi; Muhammad Ridhwan Ab. Aziz; Nur Hidayah Laili; Mohammad Noorizzuddin Nooh; Hisham Sabri; Mohamad Yazis Ali Basah (AENSI Publisher, 2024)
Non-Indexed Publication